Preferred place of death and end-of-life care for adult cancer patients in Iran: A cross-sectional study - Fereidouni, Armin; Salesi, Mahmood; Rassouli, Maryam; Hosseinzadegan, Fariba; Javid, Mohammad; Karami, Maryam; Elahikhah, Maryam; Barasteh, Salman (Frontiers in Oncology, 2022)
Background: More than 50,000 deaths in terms of cancer occur annually in Iranian hospitals. Determining the preferred place of end of life care and death for cancer patients in Iran is a quality marker for good end of life care and good death. The purpose of this study was to determine the preferred place of end of life care and death in cancer patients. Method: In 2021, the current descriptive cross-sectional investigation was carried out. Using the convenience sample approach, patients were chosen from three Tehran referral hospitals (the capital of Iran). A researcher-made questionnaire with three parts for demographic data, clinical features, and two questions on the choice of the desired location for end-of-life care and the death of cancer patients served as the data collecting instrument. Data were analyzed using SPSS software version 18. Result: The mean age of patients participating in the study was 50.21±13.91. The number of 390 (69.6%) of the patients chose home and 170 (30.4%) patients chose the hospital as the preferred place of end of life care. Choosing the home as a preferred place for end of life care had significant relationship with type of care (OR = .613 [95% CI: 0.383 - 0.982], P = .042), level of education (OR = 2.61 [95% CI: 1.29-5.24], P = 0.007), type of cancer (OR = 1.70 [1.01-2.89], P = .049) and income level (Mediate: (OR: 3.27 (1.49, 7.14), P = .003) and Low: (OR: 3.38 (1.52 -7.52), P = .003). Also, 415 (75.2%) patients chose home and 137 (24.8%) patients chose hospital as their preferred place of death. Choosing the home as a preferred place of death had a significant relationship with marriage (OR = 1.62 [95% CI: 1.02- 2.57], P = .039) and Time to diagnostic disease less than 6 months (OR = 1.62 [95% CI: 0.265 - 0.765], P = .002). Conclusion: The findings of the current research indicate that the majority of cancer patients selected their homes as the preferred location for end-of-life care and final disposition.